Analisa Pendekatan Bahasa dan Historis terhadap Poligami dalam Hadis Nabi - Rohmansyah Rohmansyah (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2019)
This paper aims to determine polygamy in accordance with hadith (Prophetic ‎Tradition) where it is the second source functions as an explanation of the al-Qur’an. In ‎order to gain a more comprehensive argumentation of polygamy in hadith, researcher will ‎come through two approaches, both are linguistic and historical approach.  Based on ‎those approaches, this paper conclude that, first, polygamy during the time of Prophet ‎Muhammad was carried out solely to uphold Islam as a way of life and not in the case of ‎indulgence. Secondly, polygamy is prohibited by religion if it harms more than benefits so ‎that in order to maintain sadd al-Dzari>'ah, polygamy should not carried out. Third, ‎polygamy in hadith is allowed with the condition of justice to the wives and children ‎without any desire to seek additional income or done based on economic factors as ‎happened in the time of Arab ignorance (Jahiliyya). Thus polygamy is mentioned in ‎accordance with hadith gives a logical and systematic explanation for life and the survival ‎of a happy and prosperous family here and hereafter.‎